RESIGNIFICATION OF SYMBOLIC LOSSES IN LAVA JATO: THE CASE OF THE COMPANIES CAMARGO CORRÊA, NORBERTO ODEBRECHT AND ANDRADE GUTIERREZ - Porcionato, Gabriela Lanza [UNESP] (Univ Fed Maranhao, Centro Ciencias Humanas, 2023)
The investigation known as Lava Jato, which began in 2014, involved political parties, businessmen, state agents and the construction sector in Brazil. This article focuses on the deterioration of the image of three companies in the construction field and the strategies adopted to rebuild their reputation. Lava Jato resulted in symbolic and economic losses for the three compa-nies involved. Through qualitative research and content analysis, it is evident that the Public Prosecutor's Office's denunciations highlighted acts of corruption as rational individual conduct by the agents denoun-ced, emphasizing it as a moral deviation. After the arrest of the economic elite, com-panies began to rebuild their image through documents that emphasize integrity, trans-parency, compliance and ethics, denying corruption and the deviant behavior of the past. The analyses conclude that the com-panies have made changes to their logos, images, boards and internal documenta-tion, seeking legitimacy through ethics and transparency. This process of image recons-truction involved selective forgetting and the creation of a new public memory, allo-wing companies to choose what to remem-ber and what to forget (DOUGLAS, 1998). The change included erasing the surnames associated with Lava Jato investigation.
Keywords: Lava Jato; Investigation; Construction sector; Reconstruction of the image; Economic elite